Enhancing rangeland productivity and increasing carrying capacity with buffel grass (Cenchrus ciliaris L.), a resilient and drought-tolerant species - Louhaichi, Mounir; Belgacem, Azaiez Ouled (International Center for Agricultural Research in the Dry Areas, 2024)
Buffel grass is a drought-tolerant species able to survive in areas with less than 150mm rainfall. It is a native range species with high nutritive value and palatability, and is easy to propagate. It can be established by direct seeding, seedlings or by cuttings.